Theoretical and Experimental Evidence for the Carbon-Oxygen Group Enhancement of NO Reduction - Li, J.; Wang, Y.; Song, J.; Gao, Q.; Zhang, J.; Zhang, J.; Zhai, D.; Zhou, J.; Liu, Jian; Xu, Z.; Qian, G.; Liu, Y. (American Chemical Society, 2017)
The relation between a catalytic center and the surrounding carbon-oxygen groups influences the catalytic activity in various reactions. However, the impact of this relation on catalysis is usually discussed separately. For the first time, we proved that carbon-oxygen groups increased the reducibility of Fe-C bonds toward NO reduction. Experimentally, we compared the reductive activities of materials with either one or both factors, i.e., carbon-oxygen groups and Fe-C bonds. As a result, graphene oxide-supported Fe (with both factors) showed the best activity, duration of activity, and selectivity. This material reduced 100% of NO to N2at 300 °C. Moreover, theoretical calculations revealed that the adsorption energy of graphene for NO increased from -13.51 (physical adsorption) to -327.88 kJ/mol (chemical adsorption) after modification with Fe-C. When the graphene-supported Fe was further modified with carboxylic acid groups, the ability to transfer charge increased dramatically from 0.109 to 0.180 |e-|. Therefore, the carbon-oxygen groups increased the reducibility of Fe-C. The main results will contribute to the understanding of NO reduction and the design of effective catalysts.